Urethrectomy at the time of radical cystectomy for non-metastatic urothelial carcinoma of the bladder: a collaborative multicenter study - Laukhtina, Ekaterina; Boehm, Axelle; Peyronnet, Benoit; Bravi, Carlo Andrea; Batista Da Costa, Jose; Soria, Francesco; D'Andrea, David; Rajwa, Pawel; Quhal, Fahad; Yanagisawa, Takafumi; König, Frederik; Mostafaei, Hadi; et al. (World journal of urology, 2022)
INTRODUCTION: The optimal management of the urethra in patients planned for radical cystectomy (RC) remains unclear. We sought to evaluate the impact of urethrectomy on perioperative and oncological outcomes in patients treated with RC for non-metastatic urothelial carcinoma of the bladder (UCB). MATERIALS AND METHODS: We assessed the retrospective data from patients treated with RC for UCB of five European University Hospitals. Associations of urethrectomy with progression-free (PFS), cancer-free (CSS), and overall (OS) survivals were assessed in univariable and multivariable Cox regression models. We performed a subgroup analysis in patients at high risk for urethral recurrence (UR) (urethral invasion and/or bladder neck invasion and/or multifocality and/or prostatic urethra involvement). RESULTS: A total of 887 non-metastatic UCB patients were included. Among them, 146 patients underwent urethrectomy at the time of RC. Urethrectomy was performed more often in patients with urethral invasion, T3/4 tumor stage, CIS, positive frozen section analysis of the urethra, and those who received neoadjuvant chemotherapy, underwent robotic RC, and/or received an ileal conduit urinary diversion (all p < 0.001). Estimated blood loss and the postoperative complication rate were comparable between patients who received an urethrectomy and those who did not. Urethrectomy during RC was not associated with PFS (HR 0.83, p = 0.17), CSS (HR 0.93, p = 0.67), or OS (HR 1.08, p = 0.58). In the subgroup of 276 patients at high risk for UR, urethrectomy at the time of RC decreased the risk of progression (HR 0.58, p = 0.04). CONCLUSION: In our study, urethrectomy at the time of RC seems to benefit only patients at high risk for UR. Adequate risk assessment of UCB patients' history may allow for better clinical decision-making and patient counseling.
Keywords: Radical cystectomy; Urethrectomy; nádory močové trubice; Humans; karcinom z přechodných buněk; Urethral recurrence; Urethral Neoplasms; močový měchýř; Cystectomy; lidé; uretra; Urethra; Male; nádory močového měchýře; Retrospective Studies; Urinary Bladder; Carcinoma, Transitional Cell; Bladder cancer; retrospektivní studie; cystektomie; mužské pohlaví; Urinary Bladder Neoplasms